IMPLEMENTASI FRAMEWORK CODEIGNITER PADA SISTEM INFORMASI PENDATAAN PRESTASI AKADEMIK DAN NON-AKADEMIK SISWA SMA NEGERI 4 CIBINONG BERBASIS WEB - Suci Nabila (2022)
Data about information development has turned into a fundamental need that should be met by everybody. This is on the grounds that the vast majority of an individual's day to day exercises include the assistance of information development, be it in educating, institutional work or business exercises. School is kind of training unit comprising of SD, SMP, SMA/SMK, SLB and other indistinguishable proper instruction units to accomplish public instruction objectives. Something that schools can do to work on quality as per foreordained principles is by scoring understudy accomplishment. The accomplishment information assortment led at SMAN 4 Cibinong has not run ideally in light of the fact that it is as yet traditional. The reason for this exploration is to plan a data framework detailing data about intellectual and non-scholastic accomplishments of SMA Negeri 4 Cibinong understudies in light of the CodeIgniter system site. Likewise, scientists utilize the cascade strategy in framework improvement and utilize the Unified Modeling Language (UML) in framework demonstrating and a site based stage to shape a data framework for information assortment of understudy accomplishments.